Serum concentrations and renal expressions of IL-1 and TNF-a early after hemorrhage in rats under the effect of glibenclamide - Marques, Christiane D’Oliveira [UNESP]; Diego, Luis Antonio dos Santos [UNESP]; Marcondes-Machado, Jussara [UNESP]; Amorim, Renée Lauffer [UNESP]; Carvalho, Lídia Raquel [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP]; Braz, Leandro Gobbo [UNESP]; Castiglia, Yara Marcondes Machado [UNESP] (FapUNIFESP (SciELO), 2016)
PURPOSE: To investigate changes in the serum concentration and renal expression of IL-1 and TNF-α cytokines in rats that received sevoflurane and glibenclamide prior to hemorrhage. METHODS: Two groups of sevoflurane-anesthetized Wistar rats (n=10): G1 (control) and G2 (glibenclamide, 1 μg/g i.v.); hemorrhage of 30% blood volume (10% every 10 min), with replacement using Ringer solution, 5 ml/kg/h. Serum concentrations of IL-1 and TNF-α were studied in the first hemorrhage (T1) and 50 min later (T2), renal expression, at T2. RESULTS: In serum, G1 TNF-α (pg/mL) was T1=178.6±33.5, T2=509.2±118.8 (p<0.05); IL-1 (pg/mL) was T1=148.8±31.3, T2=322.6±115.4 (p<0.05); in G2, TNF-α was T1=486.2±83.6, T2=261.8±79.5 (p<0.05); IL-1 was T1=347.0±72.0, T2= 327.3±90.9 (p>0.05). The expression of TNF-α and IL-1 in the glomerular and tubular cells was significantly higher in the G2 group. CONCLUSIONS: Hemorrhage and glibenclamide elevated TNF-α and IL-1 concentrations in serum and kidneys. High levels of TNF-α already present before the hemorrhage in the glibenclamide group may have attenuated the damages found in the kidneys after the ischemia event.
Keywords: Cytokines; Glyburide; Hemorrhage; Kidney; Rats